STRATEGY OF INTEGRATION OF LOCAL WISDOM IN THE CURRICULUM OF HIGHER EDUCATION - Loso Judijanto; Rengga Yudha Santoso; Lensi Megah Retta; Suhana Sarkawi (Adisam Publisher, 2024)
In a context of globalization that is increasingly eroding local values and cultural identities, the integration of local wisdom into higher education curricula offers an innovative solution to preserve and enhance those values. The research aims to identify and analyse effective strategies in integrating local intelligence into the curriculum, as well as measure its impact on student character education and multicultural abilities. The methods used in this research include examining literature by looking for literature in accordance with the context of the research. The findings show that the integration of local wisdom can be realized through several ways, such as inclusion in learning materials, the establishment of extracurricular activities that focus on local values, as well as the development of a school culture that embraces local identity. This strategy not only enriches students' learning experiences by introducing them to traditional values and practices, but also strengthens character education through the internalization of values such as diversity, tolerance, and appreciation of other cultures.